Abundance of enterovirus C in RD-L20B cell culture-negative stool samples from acute flaccid paralysis cases in Nigeria is geographically defined (2018)
Purpose. We recently showed that enteroviruses (EVs) andenterovirus species C (EV-C) in particular were abundant in faecal samples from children who had been diagnosed with acute flaccid paralysis (AFP) in Nigeria but declared to be EV-free by the RD-L20B cell culture-based algorithm. In this study, we investigated whether this observed preponderance of EVs (and EV-Cs) in such samples varies by geographical region. Methodology. One hundred and eight samples (i.e. 54 paired stool suspensions from 54 AFP cases) that had previously been confirmed to be negative for EVs by the WHO recommended RD-L20B cell culture-based algorithm were analysed. The 108 samples were made into 54 pools (27 each from North-West and South-South Nigeria). All were subjected to RNA extraction, cDNA synthesis and the WHO-recommended semi-nested PCR assay and its modifications. All of the amplicons were sequenced, and the enteroviruses identified, using the enterovirus genotyping tool and phylogenetic analysis. Results. EVs were detected in 16 (29.63 %) of the 54 samples that were screened and successfully identified in 14 (25.93 %). Of these, 10 were from North-West and 4 were from South-South Nigeria. One (7.14 %), 2 (14.29 %) and 11 (78.57 %) of thestrains detected were EV-A, EV-B and EV-C, respectively. The 10 strains from North-West Nigeria included 7 EV types, namely CV-A10, E29, CV-A13, CV-A17, CV-A19, CV-A24 and EV-C99. The four EV types recovered from South-South Nigeria were E31, CV-A1, EV-C99 and EV-C116. Conclusion. The results of this study showed that the presence of EVs and consequently EV-Cs in AFP samples declared to be EV-free by the RD-L20B cell culture-based algorithm varies by geographical region in Nigeria.